The future of healthcare reform in the United States - Malani, Anup; Schill, Michael H. (Chicago : The University of Chicago Press, 2016)
In the years since the passage of the Patient Protection and Affordable Care Act (PPACA, or, colloquially, Obamacare), most of the discussion about it has been political. But as the politics fade and the law's many complex provisions take effect, a much more interesting question begins to emerge: How will the law affect the American health care regime in the coming years and decades? This book brings together 14 leading scholars from the fields of law, economics, medicine, and public health to answer that question. Taking discipline-specific views, they offer their analyses and predictions for the future of health care reform.
Previously issued in print: 2015.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 22, 2016).
Keywords: United States; National health insurance -- Law and legislation -- United States; Medical care -- Law and legislation -- United States; Health care reform -- United States; Health and Wellbeing; United States of America, USA; Social services & welfare, criminology; Jurisprudence & general issues; Health systems & services